Effect of Fractionated Irradiation on the Hippocampus in an Experimental Model - Bálentová, S; Hajtmanová, E; Filova, B; Borbelyova, V; Lehotský, J (Klinicka onkologie, 2015)
BACKGROUND: Ionizing radiation induces altered brain tissue homeostasis and can lead to morphological and functional deficits. The aim of the present study was to investigate the short-term and long-term effect of ionizing radiation on cell population resides adult rat hippocampus. MATERIALS AND METHODS: Adult male Wistar rats received whole- brain irradiation with fractionated doses of gamma rays (a total dose of 20 Gy) and were investigated 30 and 100 days later. A combination of Fluoro-Jade C histochemistry for visualization of degenerating neurons, immunohistochemistry for detection of astrocytes and confocal microscopy were used to quantify the neurodegenerative changes in the hippocampal dentate gyrus and CA1 subfield. RESULTS: A significant increase of Fluoro-Jade C labelled neurons was seen in both of investigated areas through the whole experiment, predominantly 30 days after irradiation. Non- significant decrease of GFAP- immunoreactive astrocytes was found in the hippocampal dentate gyrus and CA1 subfield until 100 days after irradiation. CONCLUSION: Our recent results showed that radiation response of cell types resides the adult hippocampus may play contributory role in the development of adverse radiation-induced late effects.
Keywords: Glial Fibrillary Acidic Protein; Gamma Rays; gliový fibrilární kyselý protein; krysa rodu Rattus; Hippocampus; záření gama; zvířata; Immunohistochemistry; hipokampus; imunohistochemie; potkani Wistar; Rats, Wistar; Male; Astrocytes; dávka záření; frakcionace dávky záření; Rats; Radiation Dosage; Animals; astrocyty; Dose Fractionation, Radiation; mužské pohlaví